SMARCA4-deficient Thoracic Sarcomas: Clinicopathologic Study of 30 Cases With an Emphasis on Their Nosology and Differential Diagnoses. (April 2019) - Perret, Raul; Chalabreysse, Lara; Watson, Sarah; Serre, Isabelle; Garcia, Stephane; Forest, Fabien; Yvorel, Violaine; Pissaloux, Daniel; Thomas de Montpreville, Vincent; Masliah-planchon, Julien; Lantuejoul, Sylvie; Brevet, Marie; et al.
Abstract : SMARCA4-deficient thoracic sarcoma (SMARCA4-DTS) is a recently described entity with an aggressive clinical course and specific genetic alterations of the BAF chromatin remodeling complex. In the present study, we reviewed the clinical and pathologic features of 30 cases of SMARCA4-DTS, discussed its main differential diagnoses and the challenging diagnostic scenarios that the average pathologist may face. In addition, we tested the specificity of the "SMARCA4-DTS immunohistochemical signature" (co-loss of SMARCA4 and SMARCA2 with overexpression of SOX2) in a large cohort of intrathoracic malignancies. Patients ranged from 28 to 90 years of age (median: 48 y), with a marked male predominance (male:female=9:1) and they were usually smokers. Tumors were generally large compressive masses located in the mediastinum (n=13), pleura (n=5), lung (n=2) or in 2 or more of these topographies (n=10). Treatment strategies were varied, including 1 case treated with EZH2 inhibitors. Median overall survival was 6 months. Histologically, tumors were poorly differentiated frequently showing rhabdoid features. A subset of cases showed a focal myxoid stroma (7%, n=2/30) and rare cases displayed a previously unreported pattern simulating desmoplastic small round cell tumors (7%, n=2/30). Making a diagnosis was challenging when dealing with biopsy material from massively necrotic tumors and in this setting the expression of SOX2, CD34, and SALL4 proved useful. All tested cases displayed concomitant loss of SMARCA4 and SMARCA2 and most tumors expressed epithelial markers (Pan-keratin or EMA) (n=29/30), SOX2 (n=26/27), and CD34 (n=17/27). SMARCB1 expression was retained in all cases (23/23). SALL4 and Claudin-4 were expressed in a subset of cases (n=7/21 and 2/19, respectively). TTF-1 and P63 were focally expressed in 1 case each. P40 and NUT were not expressed (0/23 and 0/20, respectively) The SMARCA4-DTS immunohistochemical signature was both sensitive and specific, with only a subset of small cell carcinoma of the ovary hypercalcemic type showing overlapping phenotypes. Our study confirms and expands the specific features of SMARCA4-DTS, emphasizing the fact that they can be straightforwardly identified by pathologists. Abstract : Supplemental Digital Content is available in the text.